The Use of Caregivers' Smartphones to Assist Infants' Circadian Sleep–Wake Cycles. Issue 3 (June 2022) - Tange, Akiko; Hayashi, Mitsuo
Parents and caregivers lack knowledge regarding young children's sleep routines due to an absence of general guidelines about sleep development, and this knowledge gap has been associated with infants' sleep problems. Approximately 30% of infants develop sleep problems, including difficulty with falling asleep and night-waking. In this study, we sought to develop a new indicator of regularity in infants' circadian sleep–wake patterns. Our participants were healthy Japanese mothers and their infants ( n = 172 infants; M age = 4.9, SD = 3.5 months). Mothers used their smartphones to record the time when their infants fell asleep and woke up in their natural home environments over 7 days. We conducted least-squares spectrum analysis, a time-series analysis often used in chronobiology, to calculate the percentage variance (PVA) of the best-fitted cosine waves with a 24-hr periodicity in the infants' sleep records. We found that the PVA of the 24-hr cycles in the infants' sleep records were significantly correlated with the infants' age in months ( r = 0.554, p < 0.001), variations in their waking-up ( r = −0.316, p < 0.001) and falling asleep times ( r = −0.430, p < 0.001), and sleep duration ( r = −0.343, p < 0.001). Apart from these normative data, which are of potential comparative use by other investigators, we showed in this study that PVA data can be collected by infants' parents and caretakers through smartphones to provide parents an indicator of the regularity of an infant's 24-hr periodicity.